2022
DOI: 10.1038/s41598-022-23411-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic investigation reveals that Ishihara et al.’s (2008) STEARC effect only emerges when time is directly assessed

Abstract: The Spatial–TEmporal Association of Response Codes (STEARC) effect (Ishihara et al. in Cortex 44:454–461, 2008) is evidence that time is spatially coded along the horizontal axis. It consists in faster left-hand responses to early onset timing and faster right-hand responses to late onset timing. This effect has only been established using tasks that directly required to assess onset timing, while no studies investigated whether this association occurs automatically in the auditory modality. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…A substantial body of literature has demonstrated that the link between space and magnitudes can also manifest in indirect tasks, especially when numbers are employed (e.g., participants classify a number as even or odd rather than as smaller or larger than a reference number; for a discussion on the distinctions between direct and indirect tasks, see, e.g., Mingolo et al, 2021;van Dijck, Gevers, & Fias, 2009;Wood, Willmes, Nuerk, & Fischer, 2008). With respect to non-numerical magnitudes, the effectiveness of indirect tasks remains somewhat ambiguous; for instance, and of particular interest for the present study, recent research has documented reliable STEARC effects in direct, but not indirect, tasks (Dalmaso et al, 2023a;Mariconda et al, 2022). Therefore, future investigations could explore the feasibility of eliciting a STEARC effect when facial age is treated as an implicit dimension.…”
Section: Discussionmentioning
confidence: 89%
“…A substantial body of literature has demonstrated that the link between space and magnitudes can also manifest in indirect tasks, especially when numbers are employed (e.g., participants classify a number as even or odd rather than as smaller or larger than a reference number; for a discussion on the distinctions between direct and indirect tasks, see, e.g., Mingolo et al, 2021;van Dijck, Gevers, & Fias, 2009;Wood, Willmes, Nuerk, & Fischer, 2008). With respect to non-numerical magnitudes, the effectiveness of indirect tasks remains somewhat ambiguous; for instance, and of particular interest for the present study, recent research has documented reliable STEARC effects in direct, but not indirect, tasks (Dalmaso et al, 2023a;Mariconda et al, 2022). Therefore, future investigations could explore the feasibility of eliciting a STEARC effect when facial age is treated as an implicit dimension.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, it has been shown that space-number associations are in uenced by the implicit or explicit manipulation of numerical magnitude (e.g., Ranzini et al, 2015;Zorzi et al, 2012). Similarly, it has been recently observed that the STEARC effect is not present when temporal duration is implicitly processed, such as during timbre discrimination (Mariconda et al, 2022). Also, the effect of attentional manipulation on the processing of time is not completely consistent across studies.…”
Section: Discussionmentioning
confidence: 97%
“…However, previous findings often reported a failure in the observation of the effect when time was task-irrelevant, questioning the automaticity of the MTL activation (Aguirre & Santiago, 2017; Flumini & Santiago, 2013; Grasso et al, 2021; Santiago et al, 2007; Ulrich et al, 2012; Ulrich & Maienborn, 2010; see von Sobbe et al, 2019 for a systematic review and metanalysis. For an investigation on the automaticity of the STEARC effect on nonlinguistic stimuli see also Mariconda et al, 2022).…”
Section: Methodsmentioning
confidence: 99%